2004
DOI: 10.1007/s11661-004-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure development during high-velocity deformation

Abstract: An austenitic stainless steel was deformed at high (10 3 s Ϫ1 ) strain rates at two levels of strain by electromagnetic forces. Transmission electron microscopy (TEM) studies, X-ray diffraction analysis, and superconducting quantum-interference device (SQUID) measurements show that high strain rates induce the formation of stacking faults and twin structures, enhance the tendency for -martensite formation, and suppress the amount of ␣Ј-martensite. The increased presence of stacking faults and twin structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 10 publications
6
28
0
Order By: Relevance
“…This behavior was reported by Nikitin and Besel [26] for stainless steels tested at higher stress amplitudes. Ferreira et al [27] investigated the deformation mechanism of an austenitic stainless steel at different strain rates and concluded that an increase of the strain rate promotes the formation of stacking faults and microtwins.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior was reported by Nikitin and Besel [26] for stainless steels tested at higher stress amplitudes. Ferreira et al [27] investigated the deformation mechanism of an austenitic stainless steel at different strain rates and concluded that an increase of the strain rate promotes the formation of stacking faults and microtwins.…”
Section: Discussionmentioning
confidence: 99%
“…The fine structure, however, may be affected by strain rate. Ferreira et al [35] recently observed in TEM of 304 a significantly higher density of stacking faults and deformation twins and a lower density of perfect dislocations after straining at a strain rate of 10 3 compared to 10 Ϫ3 s Ϫ1 . They calculated that a minimum critical shear stress value of 184 MPa would enhance the nucleation of partial dislocation loops in 304 at the expense of the nucleation of perfect dislocation loops and argued that the higher stress incurred at the high strain rate accounts for the observed increase in stacking fault and deformation twin densities.…”
Section: Microstructurementioning
confidence: 98%
“…[29] They found a considerable decrease in the a¢ martensite fraction when increasing the strain rate from 10 À3 to 10 3 s À1 , due to adiabatic heating. In addition, a number of authors have done similar experiments [30,31] and concluded that adiabatic heating occurs at high strain rates. It should, however, be noted that the temperature can locally be higher than the measured macroscopic values, [32] especially if there is an autocatalytic martensitic transformation occurring in which many grains transform simultaneously, generating large amounts of local heat.…”
Section: A Strain-induced Martensitic Transformationmentioning
confidence: 99%